UJI POTENSI FUNGI PELAPUK PUTIH DARI BATANG KAYU EUKALIPTUS (Eucalyptus deglupta) SEBAGAI PENDEGRADASI LIGNIN - Ridho Perdana Ompusunggu; Edy Batara Mulya Siregar; Lutfhi Hakim (Peronema Forestry Science Journal, 2016)
Lignin is a heterogeneous polymer and complex structure consisting of koniferil alcohol, sinaphil alcohol, and kumaril alcohol making it difficult to overhauled. The complex structure of lignin with high molecular weight and insoluble in water makes lignin difficult to degrade. The purpose of this research is to get white rot fungi in biopulping process by measuring the activity of Lignin Peroxidase Enzime (LiP) at white rot fungi which is obtained. The sample of rotten eucalyptus wood taken from Taman Hutan Raya (Tahura) Berastagi. Bavendamm test have found three genus of fungi which are Phanerochaete sp. 1, Phanerochaete sp. 2, Trametes sp. The highest activity of lignin peroxidase enzyme was produced by Phanerochaete sp. 2. Key words: Eucalyptus wood, White rot fungi, Bavendamm test, lignin peroxidase enzyme